ANALISIS SENYAPAN DAN KILIR LIDAH PADA PRODUKSI UJARAN “BELIBETNYA ISYANA SARASVATI” - Nurrohmah, Fadilah (UNIB Press, 2021)
This study explains about the Pause and slip of tongue on the production of Isyana Sarasvati utterances in several video uploads on Youtube, one of which is on uploading a 20detik youtube video channel titled Isyana Sarasvati Bongkar Aib Sendiri, as well as several other videos as additional data. This analysis aims to describe the forms of the tongue's tongue and tongue and the cause of the tongue's tongue and tongue's speech that is contained in Isyana Sarasvati's speech. The analysis uses psycholingusitic studies that language is related to the mental processes that humans go through in forming an utterance. The method of data collection is done by using note- taking techniques, namely by listening to Isyana Sarasvati's utterances to be recorded, recorded and transcribed into writing. While the data analysis method uses descriptive qualitative, with tanskrispsi utterance as primary data, while books and journals as secondary data, with analysis using psycholinguistic theory from Noam Chomsky namely performance in conversation. From the analysis, it was found that silent due to breathing, and silent due to doubt. Tongue can also occur as a result of talking in a hurry, unintentionally and not concentrating. The units in the gloss of the tongue are errors in phonetic segments, syllables, and word errors.